A High-Resolution Modeling Study of the Circulation Patterns at a Coastal Embayment: Ría de Pontevedra (NW Spain) Under Upwelling and Downwelling Conditions - Cruz, Elisabet R.; Nolasco, Rita; Padin, Xosé A.; Gilcoto, Miguel; Babarro, Jose M. F.; Dubert, Jesús; Pérez, Fiz F. (Frontiers in Marine Science, 2021)
Estuarine exchange flow plays an important role in the biogeochemical properties exchange between the coastal ocean and the estuaries. Circulation patterns inside the Rias Baixas (NW Iberian Peninsula) have been widely studied, while the Ría de Pontevedra has received less attention. A high-resolution ROMS-AGRIF system configuration with three online two-way nesting domains was used and validated to enhance the knowledge about the circulation patterns of this Ría. Two representative estuarine circulation patterns were studied: a coastal upwelling event and a downwelling event associated with a maximum river runoff of 84 m3/s. An analysis using Empirical Orthogonal Functions was applied to the horizontal subtidal velocity fields at the surface layer and at 20 m depth and to the subtidal normal velocity across vertical cross-sections. Upwelling events are characterized by a reinforcement of the positive estuarine circulation, in which the surface waters outflow and deep waters inflow at the main sill of the Ría, whilst full water column inflow (outflow) is observed at the northern (southern) openings. Conversely, downwelling events induce an opposite behavior, consisting in a negative estuarine circulation with the surface (deep) inflow (outflow) at the main sill of the Ría and outflow (inflow) at the northern (southern) openings. Evidences of a front splitting two vertical clockwise circulation cells were found, associated with the ocean water subduction that enters through the surface layer under downwelling favorable winds and opposes to the inner estuarine circulation. The EOF study confirms that shelf wind forcing has an important contribution to the variability of the velocity field, inducing positive or negative estuarine like circulation. The temporal principal components (PC) of EOF analysis present correlations of 0.92 between the meridional wind component and the first mode, and 0.77 between the zonal wind component and the second mode. Third EOF mode represents the circulation during transition winds when some vorticity structures are visible. The realistic high-resolution simulation of the physical conditions at the Ría de Pontevedra provides new insights into the ocean-estuarine water exchanges and allow the visualization of recirculation processes and characteristic structures that have consequences in the marine ecosystem and in their productivity.